Toronto Workers Respond to Industrial Capitalism, 1867-1892 - Kealey, Gregory S. (University of Toronto Press, 1980)
Toronto's Industrial Revolution of the 1850s and 1860s transformed the city's economy and created a distinct working class. This book examines the workers' role in the transition to industrial capitalism and traces the emergence of a strong trade union movement in the latter half of the nineteenth century. Immigrant workers were already organized along ethnic lines and voluntary societies like the Orange Order played an informal but active part in the broad pattern of social change. Artisan groups were more directly instrumental in developing strategies to cope with the new pressures of industrial capitalism. In the period covered by this book Toronto's moulders and printers maintained and even strengthened the traditions of workers' control in the shop. The shoemakers and coopers were less successful, but the lessons of their defeats made them important early members of the Knights of Labor in the 1880s.The Knights of Labor gave new direction to labour organization. Ttiey recruited all workers regardless of skill, sex, creed, or race, and spearheaded the direct involvement of Toronto workers in electoral politics. The final chapters of the book trace the tortured path of working class politics from the early activities of the Orange Order to the emergence of a vibrant minority socialist tradition. Between I867 and I892 Toronto workers established a strong institutional base for the new struggles between craft unionism and monopoly capitalism in the early twentieth century and Kealey's detailed study of its development adds a new and important dimension to our understanding of Canadian labour history. – Publisher's description.
https://utorontopress.com/9781442682689/toronto-workers-respond-to-industrial-capitalism-1867-1892/
Keywords: History / Canada / General